Przyszłość Europy wobec zagrożeń ekologicznych - Gmerek, Liliana (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The article discusses the possible ecological and environmental threats that Europe can be faced with in the nearest future, along with the possible scenarios of the damage. The analysis presents several ideas for dealing with the threats, as well as problem-solving models, with special attention paid to Jeremy Rifkin’s ‘Third Industrial Revolution Concept’. The basis of the concept is the social aspect of the ecological change that the future may bring about. The demands and challenges that will have to be met as a result of the change are central for this article.